2018
DOI: 10.1145/3272127.3275108
|View full text |Cite
|
Sign up to set email alerts
|

Deep inertial poser

Abstract: constitutes the largest IMU dataset publicly available. We quantitatively evaluate our approach on multiple datasets and show results from a real-time implementation. DIP-IMU and the code are available for research purposes. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
132
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(161 citation statements)
references
References 71 publications
4
132
0
Order By: Relevance
“…To learn from sufficient data and incorporate variations of movement, Johnson et al (2019) synthesized accelerometer data via double-differentiation of marker trajectories from their OMC archive. Huang et al (2018) also synthesized inertial sensor data from motion capture datasets using a 3D model of the human body shape and pose (SMPL) together with a virtual sensor model. Mundt et al (2020a,b) used OMC data from several studies of their lab together with a biomechanical model to create a large simulated dataset, which was used for training feedforward neural networks to estimate joint kinematics and kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To learn from sufficient data and incorporate variations of movement, Johnson et al (2019) synthesized accelerometer data via double-differentiation of marker trajectories from their OMC archive. Huang et al (2018) also synthesized inertial sensor data from motion capture datasets using a 3D model of the human body shape and pose (SMPL) together with a virtual sensor model. Mundt et al (2020a,b) used OMC data from several studies of their lab together with a biomechanical model to create a large simulated dataset, which was used for training feedforward neural networks to estimate joint kinematics and kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…One drawback of these approaches is that additional datasets containing OMC data or SMPL poses of the movement of interest were required. Notably, Huang et al (2018) reported that combining these datasets was nontrivial. Moreover, each recorded motion trajectory led to only one synthetic sensor trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…The neck and shoulder bones move depending on the chest, while the hip bones move depending on the pelvis. Additionally, various other bones, like the feet, hands, fingers, and head, are merely extensions in the hierarchy by either increasing the number of sensors or by adopting deep learning methods like in the [28,29]. The Motion-sphere could be extended to these bone segments, depending on the application.…”
Section: Discussionmentioning
confidence: 99%
“…Existing solutions are mostly based on the installation of new cameras, either based on retro-reflective markers [4] or computer vision techniques (e.g., Microsoft Kinect) [5,6] to estimate human pose. Other common methods rely on body-worn suits with a set of IMU sensors to reconstruct body pose [3]. While effective, these approaches can increase the cost of the XR system rapidly.…”
Section: Introductionmentioning
confidence: 99%